2016
DOI: 10.1016/s0140-6736(16)00346-9
|View full text |Cite
|
Sign up to set email alerts
|

Gout

Abstract: Gout is a chronic disease of deposition of monosodium urate crystals, which form in the presence of increased urate concentrations. Although environmental factors contribute to hyperuricaemia, renal and gut excretion of urate is central to regulation of serum urate, and genetic factors are important. Activation of the NLRP3 inflammasome and release of interleukin 1β have key roles in initiation of acute gout flares. A "treat to target serum urate" approach is essential for effective gout management; long-term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
748
0
27

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 868 publications
(831 citation statements)
references
References 146 publications
4
748
0
27
Order By: Relevance
“…Reports on the joint involvement at onset of gout patients in primary care have not been found, but it must be assumed that the majority of patients initially present with intermittent monoarthritis [1,13]. The patients in the present hospital based study may represent a selected subgroup of patients with longer-standing and more severe disease than most patients seen in primary care.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Reports on the joint involvement at onset of gout patients in primary care have not been found, but it must be assumed that the majority of patients initially present with intermittent monoarthritis [1,13]. The patients in the present hospital based study may represent a selected subgroup of patients with longer-standing and more severe disease than most patients seen in primary care.…”
Section: Discussionmentioning
confidence: 96%
“…It usually affects middle aged and elderly patients with predominance in males. Typically, gout presents as an intermittent monoartritis in the foot or ankle, but with prolonged and insufficiently treated hyperuricemia gout may develop into polyarticular disease [1].…”
Section: Introductionmentioning
confidence: 99%
“…Gout is a disorder in which accumulation of needle-shaped uric acid crystals in peripheral tissues due to hyperuricemia [1]. Nonsteroidal anti-inflammatory drugs [2], steroids [3], and colchicine [4] are prescribed to suppress acute pain and inflammation, while xanthine oxidase (XOD) inhibitors such as allopurinol are used for reduction of high blood uric acid levels [5].…”
Section: Backgroundsmentioning
confidence: 99%
“…The deposition of monosodium urate crystals in tissues can be found in hyperuricemia (6.8 mg/dl). (2) Because gout occurs mainly in middle-aged or elderly men, items related to their blood uric acid levels and dietary habits are one of the common daily topics in Japan. In addition, gout has recently been seen in young people, and it has been reported that the number of patients with gout is increasing.…”
Section: Introductionmentioning
confidence: 99%